Ethnic and gender differences in drinking, smoking and drug taking among adolescents in England: a self-report school-based survey of 15 and 16 year olds. - Rodham, K; Hawton, K; Evans, E; Weatherall, R (2005)
Concern has been mounting about the increasing numbers of adolescents who (ab)use drugs, alcohol and cigarettes. The aim of this study was to establish the prevalence according to gender and ethnicity of drinking, smoking and drug-use in a representative sample of 15 and 16 year olds. The sample consisted of 6020 15- and 16-year-old pupils from 41 schools in England who completed an anonymous self-report survey. There were clear gender and ethnic differences in self-reported substance use. For example, more males than females reported drinking and drug taking. More females reported smoking, but males were more likely to be heavy smokers. Asian, Black and other boys and Black and Asian girls were less likely to report drinking during a typical week compared to White participants. Asian females were less likely to report smoking compared to White females. Cannabis was the most commonly used drug for both genders. Black males were more likely than White males to have used cannabis, opiates and other drugs. However, Asian females were more likely than their White counterparts to have used opiates, but were significantly less likely to have used cannabis. Asian males were more likely than White males to have used ecstasy. The results confirm gender differences in substance use and demonstrate that there are different patterns of substance use between ethnic groups. These findings have implications for targeting prevention campaigns through the media and educational initiatives.